On \(α\)-Continuity in Intuitionistic Topological Spaces - Ilango, Gnanambal; Albinaa, T. A. (Journal of Informatics and Mathematical Sciences, 2017)
The aim of this paper is to explore intuitionistic \(α\)-continuity and obtain their characteristics.